(untitled) (Comprehensive Journal of Science, 2025)
A study was conducted to assess the drinking water quality of the Al-Mujahed District well in Hun, Libya, using the Water Quality Index (WQI). A water sample was analyzed from the well, which has a depth of 491 meters and draws its water from the Eocene aquifer (chalky limestone and marl). The analysis included chemical, physical, and microbiological indicators. The results showed that the concentrations of Total Dissolved Solids (TDS), Calcium (Ca^2+), Magnesium (Mg^2+), Chloride (Cl^-1), and Sodium (Na^+) significantly exceeded the limits set by the Libyan Standards (2015:82) (National Center for Standards, 2015). The microbiological analysis also revealed bacterial contamination, with the Total Bacterial Count reaching 8/100 mL and E. coli at 3/100 mL, values that violate the Libyan standard of zero. The high value of the Water Quality Index (WQI) indicates that the water quality is very poor and unsuitable for drinking without treatment. The bacterial contamination is attributed to the relative proximity of the well to a septic tank (460 meters to the south), while the high concentrations of salts and hardness are attributed to the geological nature of the aquifer formations (Todd & Mays, 2005). The study recommends the necessity of dual treatment (chemical and microbial) for the water before consumption and the immediate application of protective measures for the well.